2001
DOI: 10.1097/00007890-200104270-00012
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Immunosuppression as Initial Therapy for Posttransplant Lymphoproliferative Disorder: Analysis of Prognostic Variables and Long-Term Follow-Up of 42 Adult Patients1

Abstract: Reduction in immunosuppression is an effective initial therapy for PTLD. Clinical prognostic factors may allow clinicians to identify which patients are likely to respond to reduction in immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
268
3
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(282 citation statements)
references
References 24 publications
3
268
3
4
Order By: Relevance
“…Indeed, of the three patients treated with discontinuation of immune suppressive medications alone, two died as a result of disease progression before salvage treatments such as chemotherapy could be given. These results are in contrast to a study reported by Tsai et al [19] in which 19/30 patients (74%) responded to reduction of immune suppression. However, in a much larger series, (collated from the Cincinnati Transplant Tumor Registry) only 17% of 399 complete responders had been treated with reduction of immune suppression alone [20].…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, of the three patients treated with discontinuation of immune suppressive medications alone, two died as a result of disease progression before salvage treatments such as chemotherapy could be given. These results are in contrast to a study reported by Tsai et al [19] in which 19/30 patients (74%) responded to reduction of immune suppression. However, in a much larger series, (collated from the Cincinnati Transplant Tumor Registry) only 17% of 399 complete responders had been treated with reduction of immune suppression alone [20].…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with our observation, two recent single-center studies similarly reported no effect of time to tumor development on patient survival (38,39). Several reports have suggested differences between the clinical and biological characteristics of lymphomas that develop early or late after transplantation.…”
Section: Lymphomas After Solid Organ Transplantationsupporting
confidence: 92%
“…In solid-organ transplantation, pharmacologic immunosuppression is highest in lung transplant patients in whom the incidence of PTLD approaches 10%. 15,16 Several factors have been identified in both solid-organ and stem cell transplants, which confer higher risk of developing PTLD (Table 2). In order to assess the role of T-cell immunity in the development of PTLD in allogeneic HST recipients, several groups have looked at immune reconstitution of EBV-specific cytotoxic T-cells post transplant.…”
Section: Authormentioning
confidence: 99%
“…4,16 However, cases have been reported as early as 1 week and as late as 9 years post transplant. 16 Symptoms are diverse and may be related to viral infection, mass effect, organ dysfunction, or lymphoma-related B symptoms.…”
Section: Solid-organ Transplantation Allogeneic Stem Cell Transplantamentioning
confidence: 99%
See 1 more Smart Citation